Can polyclonal intravenous immunoglobulin limit cytokine mediated cerebral damage and chronic lung disease in preterm infants?. Issue 1 (1st January 2004) - Mohan, P V; Tarnow-Mordi, W; Stenson, B; Brocklehurst, P; Haque, K; Cavendish, V; Cust, A
Abstract : Recent evidence suggests that inflammatory cytokines may play an important role in cerebral and pulmonary injury, especially in preterm infants. Immunomodulatory agents may help to limit such injury by reducing inflammation. Immunoglobulin has multiple anti-inflammatory properties and can modulate the inflammatory cytokine response. New evidence is required to test the hypotheses that prophylaxis or treatment with intravenous immunoglobulin may limit such inflammatory damage.